Analysis The Effect Of Service Quality, Price And Facilities On Customer Loyalty In Central Motor Garage: (Case Study of Pandaan Central Motor Garage) - Ennis Mufaridah (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to analyze the effect of service quality, price and facilities on customer loyalty at the Central Motor Garage in Pandaan. The research used purposive sampling, and the sample taken were 100 respondents. Analysis technique used was multiple linear regression.The results of the analysis simultaneously show that service quality, price and facilities are significant to customer loyalty and partially show service quality, price and facilities have a significant effect on customer loyalty. The results of the analysis of the coefficient of determination are known to be 74.6% variable customer loyalty can be requested by variables of service quality, price and facilities, while 25.4% are read by other variables not available in this study